Stimulation of soluble guanylate cyclase reduces experimental dermal fibrosis. Issue 6 (30th January 2012) - Beyer, Christian; Reich, Nicole; Schindler, Sonia C; Akhmetshina, Alfiya; Dees, Clara; Tomcik, Michal; Hirth-Dietrich, Claudia; von Degenfeld, Georges; Sandner, Peter; Distler, Oliver; Schett, Georg; Distler, Jörg H W
Abstract : Background: Fibrosis and vascular disease are cardinal features of systemic sclerosis (SSc). Stimulators of soluble guanylate cyclase (sGC) are vasoactive drugs that are currently being evaluated in phase III clinical trials for pulmonary arterial hypertension. Objective: To study the antifibrotic potency of sGC stimulators. Methods: The effect of the sGC stimulator BAY 41-2272 on the release of collagen from dermal fibroblasts was examined. The antifibrotic effects of BAY 41-2272 on prevention and regression of fibrosis in bleomycin-induced dermal fibrosis and in Tsk-1 mice were also studied. Telemetric blood pressure studies in conscious mice were used to study potential hypotensive effects of sGC stimulation. Results: sGC stimulation with BAY 41-2272 dose-dependently inhibited collagen release in dermal fibroblasts from patients with SSc and healthy individuals. Furthermore, BAY 41-2272 stopped the development of bleomycin-induced dermal fibrosis and skin fibrosis in Tsk-1 mice, preventing dermal and hypodermal thickening, reducing the numbers of myofibroblasts and reducing the hydroxyproline content. In addition, BAY 41-2272 was highly effective in the treatment of established fibrosis in the modified models of bleomycin-induced skin fibrosis and Tsk-1 mice. Treatment with sGC stimulators was well tolerated. Relevant antifibrotic doses of BAY 41-2272 did not affect systemic blood pressure and heart rate in mice. Conclusions: These findings demonstrate potent antifibrotic effects and good tolerability of sGC stimulators in various experimental models of SSc. Given their potential vasoactive properties, sGC stimulators may be promising candidates for the dual treatment of fibrosis and vascular disease in SSc.